GENERAL SCHEME OF DECISION SUPPORT SYSTEM FOR OPTIMIZATION OF CONDUCT MOBILE ROBOTIC MANIPULATOR - Fariza Bilyalovna Tebueva; Vladislav Borisovich Sychkov; Maxim Gennadievich Ogur (Современная наука и инновации)
This article presents an overview of intelligent decision making capability automated architecture for robotic systems. he proposed architecture is a two-level structure, where the level of solutions provides methods of constructing a plan of autonomous operation, and functional level provides interaction with the hardware of the robot means.